Solar-powered Mobile Robot for Monitoring Gas Distribution Pipe Leak Using IoT Application - Richa Watiasih; Hasti Afianti; Arif Arizal; Ahmadi Ahmadi (Fakultas Teknik Universitas Bhayangkara, 2025)
The constraints of gas distribution pipe leak monitoring robots in outdoor environments are the limited battery capacity and the method used as a monitoring system to assist the work of gas pipe leak inspection officers, which takes a long time. Therefore, the robot requires independent battery charging and real-time monitoring systems. This study resulted in a solar-powered gas distribution pipe leak monitoring robot that can provide real-time information on the robot's battery capacity and gas odor concentration data along the inspected gas distribution pipe. This robot can directly channel electrical power to the robot's battery using solar energy. This Mobile Robot uses a Photovoltaic (PV) module, Light Detection and Ranging (LiDAR), a Compass, a gas sensor, a voltage sensor, a current sensor, an ATMEGA 2560 Microcontroller, and Node MCU V3 ESP8266. The Internet of Things (IoT) application uses the Blynk application to monitor battery capacity and the concentration value of gas odor detected by the robot. The test results show that by using the PV + battery module, this mobile robot can work for more than 60 minutes compared to using only the battery for around 55 minutes. This work was successfully implemented based on IoT performance using the Blynk Application to monitor battery capacity conditions of voltage and current data and gas concentration data. It is also shown that the average delay time for sending data from voltage, current, and gas sensors to the Blynk application was around 0.226 seconds.